Uji Ekperimental Performa Mesin Diesel Mengunakan Bahan Bakar Biodiesel B35 - Hendra Purnomo; Barokah Barokah; Kriswanto Kriswanto; Iksan Saifudin; Putu Deny Darmawan; Dwi Darma Arta Kusuma (Politeknik Pelayaran Sulawesi Utara, 2024)
Diesel engines are machines that are very necessary in the industrial world, both manufacturing and transportation. How important is the existence of this diesel engine that it needs to be maintained properly to maintain its performance. With the development of diesel fuel variants, it is necessary to conduct research regarding the phenomena produced by burning biodiesel, especially the B35 type which is widely consumed in the industrial world. The aim of this research is to determine the performance of diesel engines, are specific fuel oil consumption and thermal efficiency produced by diesel engines using B35. The experimental method was applied by varying the load of 0.35 kW, 0.7 kW, 1.05 kW, 1.4 kW and 1.75 kW on an engine speed of 1500 RPM. The results show that the highest specific fuel oil consumption is at a load of 0.35 kW, that is 1361 mg/kWh, while the highest thermal efficiency at a load of 1.75 kW reaches 17.25%.